Android-Based Learning Media for Balinese Script and Its Impact on Student Achievement and Learning Autonomy - Diari, Komang Puteri Yadnya; Winantaka, Binar (Universitas Pendidikan Ganesha, 2025)
The preservation of regional scripts faces significant challenges in modern education, as students often struggle with the complexity of script structures and the lack of innovative learning methods. This situation threatens the sustainability of local literacy among younger generations. This study aims to examine the effectiveness of Android-based learning media in enhancing students' academic achievement and learning autonomy. A quantitative approach with a quasi-experimental pretest-posttest design was employed, involving 330 fourth-grade students divided into experimental and control groups. Data were collected using script literacy tests and structured questionnaires, and analyzed with t-tests and N-gain scores. The results revealed a significant increase in posttest scores among students in the experimental group compared to the control group. Additionally, most students in the experimental group demonstrated higher learning autonomy, particularly in setting learning goals, selecting materials, and independently monitoring progress. These findings confirm that Android-based learning media not only improve cognitive learning outcomes but also foster student-centered learning. The study implies the importance of developing culturally integrated and adaptive digital learning tools in primary education.